Architectural inventions : visionary drawings - Bua, Matt.; Goldfarb, Maximilian (London, United Kingdom : Laurence King Publishing, Ltd., 2012)
Born out of the drawingbuilding.org online archive, Architectural Inventions presents a stunning visual study of impossible or speculative structures that exist only on paper. Soliciting the work of architects, designers, and artists of renown--as well as emerging talents from all over the world--Maximilian Goldfarb and Matt Bua have gathered an array of works that convey architectural alternatives, by products, expansions, or critiques of our inhabited environments. Highlighting visions that exist outside of established channels of production and conventions of design, Architectural Inventions showcases a multiplicity in concept and vision, fantasy and innovation.
Introduction: VISIONARY DRAWING BUILDING -- Maximilian Goldfarb, Matt Bua; The Beginning: DRAWING: A SILENCE -- Daniel Berry; The Beginning: TESSERACT HOUSE -- Paul Laffoley; Essays; Reconstruction: RE: CONSTRUCTIONS, an INVITATION -- Angela Co; Re-Future: DOOMSDAY DOMES -- Eva Diaz; TechnoSustainable: TECHNOSUSTAINABLE -- Stephen Hren; Radical Lifestyle: EXCERPTS from the GLOSSARY -- J. Morgan Puett; Microcommunity: JANUARY 2, 2000 -- Suzanne Snider; Utility: ON INFRASTRUCTURE -- Darryl Chen; Mobile: P3 and the SIGN for RECYCLE -- Axel Bishop Encampment: DESIGN for the APOCALYPSE -- John McMorroughSurvival: ON an ARCHITECTURE of SURVIVAL -- Farrah Karapetian; Healing: LEARNING HOW to SIT and STAND -- Aki Ishida; Worship: WORSHIP -- Joshua Tonies; Museum/Pavilion: 2015 or FUNCTION for the FUNCTIONLESS -- Anthony Graves; Intervention: OPEN GOAL for REDS -- Nick Tobier; Adapt: From MANUAL: TUNNEL into TOWER -- Maximilian Goldfarb; Fort: FORT -- Mary Walling Blackburn; Interstice: INTERSTITIAL SPACES -- Thomas Micchelli; Clandestine: The CLANDESTINE BUILDING -- Michael Cataldi; Misuse: IDLE TIMES -- Jocko Weyland -- A USER'S GUIDE to CYCLONOPOLIS -- Jeff BylesDrawings; Reconstruction; TechnoSustainable; Habitat; Radical Lifestyle; Microcommunity; Utility; Mobile; Survival; Healing; Worship; Museum/Pavillion; Intervention; Adapt; Fort; Interstice; Clandestine; Misuse; Notes on Contributors.
Includes index.
Keywords: UNBUILT ARCHITECTURAL PROJECTS